Dyeing Behaviour of g-Irradiated Cotton Using Amaltas (Cassia fistula) Bark Extracts - Adeel, Shahid; Rehman, Fazal-ur-; Gulzar, Tahsin; Ahmad Bhatti, Ijaz; Qaiser, Summia; Abid, Anam (Asian Journal of Chemistry, 2012)
Amaltas bark (Cassia fistula) has been used as natural colourant for dyeing of un-irradiated and irradiated cotton fabric. Both cotton fabric and dye powder has been exposed to absorbed doses of 2, 4, 6, 8 and 10 kGy using Cs 137 g-irradiator. Dyeing parameters such as temperature and time were optimized. To improve colour strength pre and post mordanting using copper and iron as mordants was carried out. Suggested ISO standard methods for colour, fastness to light, washing and rubbing were employed to observe fastness properties. It is observed that dyeing of irradiated fabric at 50 ºC for 50 min using Cu as pre-mordant (4 %) has not only given good colour strength with darker shades but also acceptable fastness properties are obtained. It is concluded that g-irradiation has a promising effect in improvement of colour strength and colourfastness properties and it can be applied on other fabrics dyed with other natural colourants.